2003
DOI: 10.2151/jmsj.81.1353
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Characteristics in Mid-Latitude East Asia as Observed by TRMM PR and TMI

Abstract: Precipitation radar and microwave radiometer data from the Tropical Rainfall Measuring Mission (TRMM) satellite during the spring and summer months of 1998 are used to study the precipitation characteristics in the mid-latitude East Asia region (20 -40 N, 100 -140 E), with particular emphasis on comparing the differences between stratiform and convective rains, and between rains during spring and summer. The characteristics in the mid-latitude are also compared with those in the tropics. The two-season mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 29 publications
1
25
0
2
Order By: Relevance
“…In this article, 10-year (1998-2007) TRMM PR rain products (2A25) are used to determine properties of convective and stratiform rain [21]. Other precipitation in 2A25 accounts for about 1% of the rainfall amount and 5.8% of the rain area [22,23]. Therefore, it is common to only consider TRMM convective and stratiform rain in studying the spatial distribution [19,23], seasonal variation [24][25][26] and diurnal cycle [27,28] of precipitation.…”
Section: Datasets and Methodsmentioning
confidence: 99%
“…In this article, 10-year (1998-2007) TRMM PR rain products (2A25) are used to determine properties of convective and stratiform rain [21]. Other precipitation in 2A25 accounts for about 1% of the rainfall amount and 5.8% of the rain area [22,23]. Therefore, it is common to only consider TRMM convective and stratiform rain in studying the spatial distribution [19,23], seasonal variation [24][25][26] and diurnal cycle [27,28] of precipitation.…”
Section: Datasets and Methodsmentioning
confidence: 99%
“…Applying the cloud classification scheme to the observed rainy satellite FOVs yielded a distribution of about 12% convective, 14% mixed and 74% nonconvective with relatively little variability across the oceanic regions (Table 2). Although overall the convective clouds in all regions occupy a small portion, their contribution to total rain is significant because the mean rain rate is at about six times greater than that of stratiform rain [ Fu and Liu , 2003].…”
Section: Datamentioning
confidence: 99%
“…However, researches aiming at the global scale are not feasible due to the limited location of measurements provided by individual radars and finite quantities of experiments. Fu et al analyzed the vertical profiles of precipitation by employing the TRMM PR data over East Asia in 1998 and presented the result that significant difference exists between convective and stratiform precipitation and there is a significant seasonal variability in mean profiles of mid-latitude precipitation caused by the different heights of freezing level in each season [41] . Another relevant study addressing the detailed variation in the vertical structure of precipitation indicated that on a logarithm scale the slopes of the rain profiles are approximately constants if the profiles are divided vertically into 3 or 4 layers, i.e.…”
Section: Structures Of Precipitating Cloudmentioning
confidence: 99%